Psychological and behavioural characteristics that distinguish street gang members in custody - Alleyne, Emma (Legal and criminological psychology, 2016)
Purpose. Using social dominance theory, the primary aim of this study was to examine the attitudes and beliefs that reinforce status hierarchies and facilitate aggressive behaviour within and between gangs. The aim was also to determine whether these socio-cognitive processes distinguished gang-involved youth from non-gang offenders in a custodial setting. Methods. Gang-involved youth and non-gang offenders were recruited from a young offender institution located in the United Kingdom. Questionnaires assessing psychological (i.e., moral disengagement strategies, anti-authority attitudes, hypermasculinity, and social dominance orientation) and behavioural (i.e., group crime) characteristics were administered individually. We hypothesized that gang-involved youth would be affiliated with groups who engaged in more criminal activity than non-gang offenders, and that they would report higher levels of endorsements than non-gang youth across all of the psychological measures. Results. We found that gang-involved youth were affiliated with groups who engage in more crimes than non-gang offenders. We also found that social dominance orientation was an important factor related to gang involvement along with measures assessing group-based hierarchies such as hypermasculinity, anti-authority attitudes, and the moral disengagement strategies displacement of responsibility, dehumanization, and euphemistic labeling. Conclusions. These findings fit within a social dominance theoretical framework as they highlight key psychological factors that feed into perceived status-driven hierarchies that distinguish gang members from other types of offenders. These factors could be key to developments in treatment provision within custodial settings.